Characterization of a P1-bacteriophage-like plasmid (phage-plasmid) harbouring blaCTX-M-15 in Salmonella enterica serovar Typhi. Issue 12 (5th December 2022) - Greig, David R.; Bird, Matthew T.; Chattaway, Marie Anne; Langridge, Gemma C.; Waters, Emma V.; Ribeca, Paolo; Jenkins, Claire; Nair, Satheesh
Abstract : Antimicrobial-resistance (AMR) genes can be transferred between microbial cells via horizontal gene transfer (HGT), which involves mobile and integrative elements such as plasmids, bacteriophages, transposons, integrons and pathogenicity islands. Bacteriophages are found in abundance in the microbial world, but their role in virulence and AMR has not fully been elucidated in the Enterobacterales . With short-read sequencing paving the way to systematic high-throughput AMR gene detection, long-read sequencing technologies now enable us to establish how such genes are structurally connected into meaningful genomic units, raising questions about how they might cooperate to achieve their biological function. Here, we describe a novel 98 kbp circular P1-bacteriophage-like plasmid termed ph681355 isolated from a clinical Salmonella enterica serovar Typhi isolate. It carries bla CTX-M-15, an IncY plasmid replicon ( repY gene) and the IS EcP1 mobile element and is, to our knowledge, the first reported P1-bacteriophage-like plasmid (phage-plasmid) in S . enterica Typhi. We compared ph681355 to two previously described phage-plasmids, pSJ46 from S . enterica serovar Indiana and pMCR-1-P3 from Escherichia coli, and found high nucleotide similarity across the backbone. However, we saw low ph681355 backbone similarity to plasmid p60006 associated with the extensively drug-resistant S . enterica Typhi outbreak isolate in Pakistan, providing evidence of an alternative route for bla CTX-M-15 transmission. Our discovery highlights the importance of utilizing long-read sequencing in interrogating bacterial genomic architecture to fully understand AMR mechanisms and their clinical relevance. It also raises questions regarding how widespread bacteriophage-mediated HGT might be, suggesting that the resulting genomic plasticity might be higher than previously thought.